Susceptibility to multiple sclerosis: interplay between genes and environment. - Willer, C; Ebers, G (2000)
Multiple sclerosis is a complex trait of unknown etiology. Epidemiological data have shown that susceptibility to multiple sclerosis is determined by both genetic and environmental factors. It is unknown whether the clinical subcategories of multiple sclerosis are separate diseases with separate etiologies and causes. Recent theories of the pathogenesis of multiple sclerosis and candidate genes are discussed. Other potential nonchromosomal factors involved in multiple sclerosis susceptibility such as mitochondrial DNA and viral factors such as Chlamydia pneumoniae are reviewed.